2021
DOI: 10.3390/ijms221910301
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wnt/β-Catenin Signaling Sensitizes Esophageal Cancer Cells to Chemoradiotherapy

Abstract: The standard treatment of locally advanced esophageal cancer comprises multimodal treatment concepts including preoperative chemoradiotherapy (CRT) followed by radical surgical resection. However, despite intensified treatment approaches, 5-year survival rates are still low. Therefore, new strategies are required to overcome treatment resistance, and to improve patients’ outcome. In this study, we investigated the impact of Wnt/β-catenin signaling on CRT resistance in esophageal cancer cells. Experiments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Inhibition of β‐catenin is an effective strategy for tumor treatment. For example, many studies have reported that inhibition of Wnt/β‐catenin signaling can suppress esophageal cancer, triple‐negative breast cancer, and pancreatic cancer 15–17 . Corresponding to this, the study demonstrated that β‐catenin peptide inhibitors have significant antimetastatic and antiproliferative effects on HT‐29 cells, as well as promote apoptosis in HT‐29 cells.…”
Section: Discussionmentioning
confidence: 80%
“…Inhibition of β‐catenin is an effective strategy for tumor treatment. For example, many studies have reported that inhibition of Wnt/β‐catenin signaling can suppress esophageal cancer, triple‐negative breast cancer, and pancreatic cancer 15–17 . Corresponding to this, the study demonstrated that β‐catenin peptide inhibitors have significant antimetastatic and antiproliferative effects on HT‐29 cells, as well as promote apoptosis in HT‐29 cells.…”
Section: Discussionmentioning
confidence: 80%
“…As the key point of classical Wnt signaling pathway, CTNNB1 gene can bind with transcription factors TCF/LEF, thus forming a complex to promote the up-regulation of target genes, which finally causes a series of biological changes in cells and tissues ( Nabais et al, 2003 ; Wu et al, 2016a ). Through activation of Wnt signaling pathway, CTNNB1 involves in the early process of malignant tumors ( Spitzner et al, 2021 ; Yu et al, 2021 ), including liver cancer, gastric cancer and EC with high incidence, which are all present in ectopic expression of CTNNB1.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin signalling pathway has been found to be aberrantly activated in a variety of tumours. It has been demonstrated that inhibition of Wnt/β-catenin signalling increases the sensitivity of esophageal cancer cells to radiotherapy ( Spitzner et al, 2021 ). Cao et al (2020) used a high-resolution multiomics approach to map the epigenetic landscape of ESCC, suggesting that the epigenetically mediated Wnt/β-catenin signalling pathway is a potential oncogenic driver of ESCC.…”
Section: Epigenetically Linked Pathways In Esophageal Cancermentioning
confidence: 99%